Evaluation of Hepatoprotective Effect of Vanillin in Isoniazid-Rifampicin Induced Hepatocellular Damage - Tiwari, Rashint; Chourasia, Ayushi; Chaturvedi, Aman; Ganeshpurkar, Aditya; Dubey, Nazneen (Free Radicals and Antioxidants)
Objectives: Natural products are greatly acknowledged for antioxidant and hepatoprotective effects. Vanillin has been studied for radical scavenging effect. The aim of this study was to examine hepatoprotective effect of vanillin against isoniazid and rifampicin induced liver damage in rats. Methods: Wistar rats were used in present study. All the animals study protocols were duly approved by Institutional Animal Ethics Committee of the Institute. Hepatotoxicity was induced by administration of against isoniazid (50 mg/kg) and rifampicin (100 mg/kg) for 14 days. Vanillin was used in the dose of 50, 100 and 200 mg/kg body weight. At the end of study blood was collected and biochemical studies were performed to assess antioxidant status. Results: Oral administration of vanillin at test doses (50, 100 and 200 mg/ kg body weight) resulted in restoration of AST, ALT and ALP. There was a notable decrease in production of SOD and catalase. Conclusion: In the present study, vanillin demonstrated a notable hepatoprotective effect. The protective efficacy of vanillin is possibly because of radical scavenging and antioxidant property.
Keywords: Liver; Toxicity; Antitubercular; Peroxidation; Vanillin